Morphological and Biochemical Characterization of Bacteria Isolated from Fresh and Salted Hilsa, Tenualosa ilisha (Hamilton, 1822) - Rohomania, Tahara; Saha, Mihir Lal; Hossain, Anwar; Rahman, Mohammad Shamsur (Bangladesh Journal of Microbiology, 2016)
Morphological and biochemical characterization of different bacteria isolated from eight fresh and salted hilsa collected from four fish markets namely Palashi Bazaar, Karwan Bazaar, Anando Bazaar and New Market of Dhaka city was carried out. Five types of bacteriological culture media namely nutrient agar as generalized complex medium, EMB agar medium for coliform, SS agar for Salmonella-Shigella, MSA for Staphylococcus and TCBS for Vibrio were used to isolate the bacteria associated with the hilsa. In salted hilsa, no microbial growth was observed on SS and TCBS agar plate. A total of 66 bacterial isolates were obtained in the study where detail study of 24 strains (12 Gram positive and 12 Gram negative) using morphological and biochemical characterization was conducted. Variable morphological and biochemical properties of the isolated strains were observed. Gram positive bacteria such as Listeria monocytogenes, Bacillus megaterium, B. marinus, Planococcus citreus, Micrococcus varians, M. nishinomiyaensis, Staphylococcus lentus, S. epidermidis, S. aureus and Gram negative bacteria such as Salmonella paratyphi, Salmonella spp., Proteus morganii, P. vulgaris, Vibrio sp., Halobacterium sp. were presumptively identified in the current study. Presence of these bacteria in fish indicates the possibility of occurrence of food poisoning. So, care should be taken during handling and consumption of hilsa whether fresh or salted as it carries pathogenic strains of bacteria of public health concern. Bangladesh J Microbiol, Volume 32, Number 1-2,June-Dec 2015, pp 7-13